The mediating roles of pre-competitive coping and affective states in the relationships between coach-athlete relationship, satisfaction and attainment of achievement goals - González-García, Higinio; Martinent, Guillaume; Nicolas, Michel (International Journal of Sport and Exercise Psychology, 2023)
The study is aimed to explore the relationship between coach-athlete relationship, precompetitive coping and affective states, satisfaction and attainment of achievement goals. A sample of 567 French athletes (Mage = 22.10; SD = 5.66; 377 men and 190 women) involved in 75 training groups participated in the study and completed a series of self-report measures in a temporal design with three measure points. Results of multilevel analyses revealed that the coach-athlete dyad (level 2; between-person level of analysis or training groups) and task-oriented coping (level 1; within person level of analysis or individuals) significantly predicted goal attainment (level 1). Moreover, the results of the Sobel test revealed that task-oriented coping (level 1) marginally mediated the relationship between coach-athlete dyad (level 2) and sport satisfaction (level 1). Besides, the coach-athlete dyad (level 1) and Intensity of positive affect (PA) mediated the relationship between coach-athlete dyad and goal attainment. Finally, the coach-athlete dyad (level 1) and Intensity of PA mediated the relationship between coach-athlete dyad and satisfaction (level 1). In conclusion, the display of Coach-Athlete relationship strategies may enhance higher levels of precompetitive task-oriented coping, intensity of PA, goal attainment and satisfaction. Subsequently, coaches and practitioners should focus their training on enhancing coach-athlete relationship as a crucial part of training in order to perform in competitions.
Keywords: competitive settings; coaching; goals; wellbeing; JCR; Scopus